2021
DOI: 10.3892/ijmm.2021.4939
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog signaling pathway in gynecological and genitourinary cancer (Review)

Abstract: Cancers of the urinary tract, as well as those of the female and male reproductive systems, account for a large percentage of malignancies worldwide. Mortality is frequently affected by late diagnosis or therapeutic difficulties. The Sonic Hedgehog (SHH) pathway is an evolutionary conserved molecular cascade, which is mainly associated with the development of the central nervous system in fetal life. The present review aimed to provide an in-depth summary of the SHH signaling pathway, including the characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 208 publications
1
12
0
Order By: Relevance
“…Furthermore, higher mRNA level of GLI2 and GLI3 was observed in 44 and 36 patients with ccRCC, respectively ( Table III ). High (~48-fold upregulation) GLI1 gene expression was observed in tumor tissues of 44 patients with ccRCC ( Table III ), and this also acts as positive feedback in the SHH signaling pathway ( 6 ). Although the mRNA levels of PTCH1 , the second gene involved in negative feedback regulation of the SHH signaling pathway ( 6 ), were not quantitatively changed in direct comparison with normal kidney samples, increased levels were observed in tumor ccRCC tissues of younger patients (<64 years of age; Table III ), which is in line with our previous research ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, higher mRNA level of GLI2 and GLI3 was observed in 44 and 36 patients with ccRCC, respectively ( Table III ). High (~48-fold upregulation) GLI1 gene expression was observed in tumor tissues of 44 patients with ccRCC ( Table III ), and this also acts as positive feedback in the SHH signaling pathway ( 6 ). Although the mRNA levels of PTCH1 , the second gene involved in negative feedback regulation of the SHH signaling pathway ( 6 ), were not quantitatively changed in direct comparison with normal kidney samples, increased levels were observed in tumor ccRCC tissues of younger patients (<64 years of age; Table III ), which is in line with our previous research ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in vivo treatment of cancer-bearing mice with both GANT61 and perifosine was found to be associated with higher renal cancer suppression than treatment with either of these agents alone, and this is reflected by the reduction in tumor volume and increased immunoreactivity of an apoptotic marker (cleaved-caspase 3) in cancer tissues ( 17 ). It has been demonstrated that activation of the MAPK/ERK signaling pathway stimulates the transcriptional activity of GLIs in gastric cancer ( 6 ). Therefore, due to the possible involvement of other signaling pathways in the regulation of transcriptional activity of GLIs in kidney cancer, the antitumor properties of GANT61 appear to be weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we examined the expression of the SHH signaling-related genes, Shh , Ptch , and Smo , after LA treatment, we observed that only Shh exhibited increased expression ( Figure 1B ). GLIs are responsible for transmitting SHH signals to the nucleus and inducing gene expression [ 15 ]. The expression pattern of GLIs may be involved in the specific signal formation by LA.…”
Section: Resultsmentioning
confidence: 99%
“…SHH is overexpressed in CRCs [ 13 ], and activation of SHH signaling correlates with the metastatic potential of CRCs [ 14 ]. The hedgehog (Hh) pathway involves signaling via one of the three Hh ligands (SHH, Indian HH [IHH], and Desert HH [DHH]) to the glioma-associated oncogene (GLI) transcription factors [ 15 ]. This process is mediated by interplay between the inhibitory receptor, patched (PTCH1), and the activating receptor, smoothened (SMO); the process is also influenced by protein kinase A (PKA), and cyclic adenosine monophosphate (cAMP).…”
Section: Introductionmentioning
confidence: 99%